A new species and a new combination of Coltricia (Hymenochaetaceae, Basidiomycota) from China - Zeng, Guang-Yu; Wu, Ying-Da; Zhu, An-Hong; Zhang, Xin (Phytotaxa, 2025)
A new species, Coltricia hainanensis, is described from tropical China based on morphology and phylogenetic analysis inferred from combined ITS and nLSU sequences data. Coltricia hainanensis is characterized by annual, centrally stipitate basidiomata with concentric zones, a monomitic hyphal system, and thick-walled, verrucose basidiospores (7.3–11 × 4–5.2 µm) that are predominantly oblong-ellipsoid to mango-shaped (Q = 1.8–2.1). In addition, a new combination, C. yunnanensis, is proposed based on phylogenetic analysis, and a key to the known Coltricia species in China is given to facilitate species identification.